PRACTICE OF COOPERATION OF HIGHER EDUCATIONAL INSTITUTION AND EMPLOYERS` ORGANIZATIONS IN RUSSIA ON THE EXAMPLE OF THE DEPARTMENT OF PERSONNEL MANAGEMENT OF THE “STATE UNIVERSITY OF MANAGEMENT” - T. V. Suvalova (Вестник университета, 2019)
The experience of cooperation with organizations of employers of the Department of “Personnel Management” of the State University of Management has been explored. The main areas of interaction have been listed, such as the creation and maintenance of a club of graduates of the department, work with students of the center of additional professional education, holding round tables, master classes by employers on the territory of the university, participation in the career day, organization and holding of the annual All-Russian Inter-University Personnel Forum named after A. Ya. Kibanov. Close cooperation with employers ensures the integration of the educational process into practice and vice versa. As a result of cooperation, according to the data of HeadHunter Сompany, the Department of Personnel Management took honorable third place in the list of winners, releasing the most demanded specialists in the field of training “personnel management” to the labor market.